2018
DOI: 10.1111/1759-7714.12904
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of long non‐coding RNAs in esophageal squamous cell carcinoma reveals their potential role in invasion and metastasis

Abstract: BackgroundA high lymphatic metastasis rate and strong local invasive ability are the key characteristics of esophageal squamous cell carcinoma (ESCC) that affect patient survival, and long non‐coding RNAs (lncRNAs) may play a crucial role. We performed genome‐wide analysis of lncRNAs to identify novel biomarkers associated with local invasion and lymphatic metastasis in ESCC.MethodsSix pairs of ESCC tumor and para‐tumor tissues were subjected to microarray analysis to identify differentially expressed lncRNAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In literature reports, lncRNA expression signatures can predict survival in patients with lung adenocarcinoma, colorectal cancer and hepatocellular carcinoma [42][43][44]. In ESCC patients, although many studies on lncRNA expression profiles have been reported, most studies only employed a few paired cancer and non-cancer samples [45,46], and only one 3-lncRNA prognostic signature has been identified in 119 esophageal cancers and paired non-cancerous tissues with microarray method [24]. In the present study, we detected 141 ESCC samples with the custom lncRNA microarray and identified a 7-lncRNA signature for predicting survival of patients with ESCC in the training cohort, and validated it with RT-PCR in the independent cohort, suggesting that this 7-lncRNA signature is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…In literature reports, lncRNA expression signatures can predict survival in patients with lung adenocarcinoma, colorectal cancer and hepatocellular carcinoma [42][43][44]. In ESCC patients, although many studies on lncRNA expression profiles have been reported, most studies only employed a few paired cancer and non-cancer samples [45,46], and only one 3-lncRNA prognostic signature has been identified in 119 esophageal cancers and paired non-cancerous tissues with microarray method [24]. In the present study, we detected 141 ESCC samples with the custom lncRNA microarray and identified a 7-lncRNA signature for predicting survival of patients with ESCC in the training cohort, and validated it with RT-PCR in the independent cohort, suggesting that this 7-lncRNA signature is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve survival rate and the detection and treatment of early-stage ESCC, more effective therapeutic tools are required, including the identification of novel diagnostic and prognostic biomarkers. Recent studies that have focused on the abnormal expression of lncRNAs have revealed a new investigative approach to the pathological changes observed in ESCC, and have also indicated that the search for novel biomarkers may hold promise for ESCC diagnosis and prognosis (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“… 2 ESCC ranks eighth highest in incidence and sixth highest in mortality rate among all cancers globally. 3 ESCC is one of the most prevalent gastrointestinal malignancies. The early symptoms of esophageal cancer are not obvious; when identified, the disease tends to be in the middle or late stages.…”
Section: Introductionmentioning
confidence: 99%